Mechanical properties and residual stresses in ZrB2–SiC spark plasma sintered ceramic composites. Issue 7 (June 2016) - Stadelmann, R.; Lugovy, M.; Orlovskaya, N.; Mchaffey, P.; Radovic, M.; Sglavo, V.M.; Grasso, S.; Reece, M.J.
Abstract: ZrB2 -17 vol% SiC, ZrB2 -32 vol% SiC, and ZrB2 -45 vol% SiC ultra-high temperature particulate ceramic composites were sintered using Spark Plasma Sintering (SPS). The mechanical performance of the ZrB2 –SiC composites was investigated using 4-point bending to determine their instantaneous flexural strength and fracture toughness. Resonant Ultrasound Spectroscopy was used to determine the Young's, shear, and bulk moduli as well as Poisson's ratio of all examined composites. The distribution of thermal residual stresses and the effect of applied external load on their re-distribution was studied using micro-Raman spectroscopy. Piezospectroscopic coefficients were determined for all three ZrB2 –SiC ceramic composites and their experimentally obtained values were compared with the piezospectroscopic coefficients both published in the literature and calculated theoretically. Finally an attempt was made to evaluate the redistribution of thermal residual stresses under external applied stress in order to estimate their contribution to the mechanical behavior of the material.